DIAGNOSIS PENYAKIT GUGUR DAUN KARET (Hevea brasiliensis Muell. Arg.) - Alchemi Putri Juliantika Kusdiana (Pusat Penelitian Karet - PT. Riset Perkebunan Nusantara, 2020)
One of the causal of the low rubber production is the presence of plant diseases. Important diseases in rubber plants generally cause symptoms of leaf fall, due to Colletotrichum spp., Corynespora sp., and Oidium sp. Currently, there is an incidence of new rubber leaf fall disease with symptoms that are different from the diseases previously found in rubber plantations. This disease is widespread in Sumatra, Kalimantan, and Southeast Asia. There are many suspicions about the pathogens that cause the disease, but there is no precise diagnosis. Therefore, an accurate diagnosis is needed as a basis for determining an effective and efficient disease control strategy. This research was carried out to determine the causal agents of leaf fall disease with symptoms of round leaf spots that can cause leaf fall. Diagnosis was carried out by isolating the pathogen from several rubber clones, inoculating the pathogen to healthy rubber plants, identifying morphologically and molecularly, and re-isolating from inoculated plants. The results of Koch's postulates and morphological and molecular identification determined that the causal agents of leaf fall disease at rubber plants with round spots was the fungus Pestalotiopsis microspora.